Heat-shrinkable polyester film, heat-shrinkable label, and packaging material

The use of a specifically formulated copolymer polyester raw material addresses the issue of unstable shrinkage rates in heat-shrinkable polyester films after aging, resulting in a film with high and stable shrinkage performance and low stress, suitable for various packaging applications.

JP7662006B2Active Publication Date: 2025-04-15TOYOBO CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023171513
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-03
Filing Date
2023-10-02
Publication Date
2025-04-15
Estimated Expiration
2039-07-26

AI Technical Summary

Technical Problem

Existing heat-shrinkable polyester films exhibit high natural shrinkage rates and reduced hot water shrinkage rates after aging, leading to poor shrinkage finish and label distortion, especially in low heat transfer coefficient environments.

Method used

A copolymer polyester raw material with specific composition and processing conditions, including a high content of neopentyl glycol and diethylene glycol, is used to produce a heat-shrinkable polyester film with controlled shrinkage rates and stress, maintaining stability even after aging.

Benefits of technology

The resulting heat-shrinkable polyester film achieves a high and stable shrinkage rate, low shrinkage stress, and excellent thickness uniformity, ensuring consistent and high-quality shrinkage performance both before and after aging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662006000001
    Figure 0007662006000001
  • Figure 0007662006000002
    Figure 0007662006000002
  • Figure 0007662006000003
    Figure 0007662006000003
Patent Text Reader

Abstract

To provide a heat-shrinkable polyester film which has a high heat shrinkage ratio in a main shrinkage direction, exhibits a small heat shrinkage ratio in a non-shrinkage direction, and has a small change in a shrinkage ratio before and after aging, and a raw material for producing the heat-shrinkable polyester film.SOLUTION: A copolymerization polyester raw material for an amorphous film satisfies the following requirements (1) to (4), and is used for film production. (1) When the raw material contains ethylene terephthalate as a main component, and the total amount of a glycol component in the total polyester resin component is 100 mol%, the raw material contains 15 mol% or more and 30 mol% or less of neopentyl glycol. (2) The raw material contains 7 mol% or more and 15 mol% or less of a constitutional unit derived from diethylene glycol in 100 mol% of the total amount of the glycol component in the total polyester resin component. (3) Intrinsic viscosity of the raw material is 0.60 dl / g or more and less than 0.70 dl / g. (4) A glass transition temperature is 60°C or higher and 70°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-shrinkable polyester film suitable for use in heat-shrinkable labels, a method for producing the same, and raw materials for the film. [Background technology]

[0002] In recent years, polyester-based heat-shrinkable films, which have high heat resistance, are easy to incinerate, and have excellent solvent resistance, have come to be widely used as shrink labels for applications such as label packaging, cap seals, and accumulated packaging that combine the protection of glass or plastic bottles and the like with product display, and the amount of these films used is tending to increase along with the increase in PET (polyethylene terephthalate) bottle containers, etc.

[0003] So far, heat-shrinkable polyester films that shrink significantly in the width direction have been widely used. In addition, in order to improve the shrink finish, it is also known to have a negative shrink rate in the non-shrinkable longitudinal direction (so-called stretching by heating) (Patent Document 1).

[0004] A disadvantage of heat shrinkable films with a high shrinkage rate so that they can be used with various containers is that the natural shrinkage rate increases after storage at room temperature (after aging) (Patent Document 2, Patent Document 3), and the hot water shrinkage rate decreases when measured at 70°C. In Patent Document 2, a biaxially stretching production method is adopted, and the natural shrinkage rate is improved by performing cooling reinforcement after biaxial orientation and longitudinal stretching, but the hot water shrinkage rate before and after aging when measured at 70°C is not described. In Patent Document 3, the natural shrinkage rate is improved, but technical knowledge about improving the natural shrinkage rate is unclear. In addition, the value of the 70°C shrinkage rate before and after aging is unclear. If the decrease in the 70°C shrinkage rate is large, the initial shrinkage rate when shrinking is different, and there is a problem that the shrink finish is poor. In particular, in a shrinkage device using hot air with a low heat transfer coefficient, if the initial shrinkage rate due to the hot air is different, it is not preferable because insufficient shrinkage and distortion of the label occurs at the time of finishing.

[0005] A film that is heat-shrinkable in the longitudinal direction as described in Patent Document 4 is generally stretched between rolls using the speed difference between heated rolls, and therefore the deformation speed during stretching is faster than that of a film that shrinks in the width direction. If the deformation speed during stretching is fast, a necking force is generated in the direction perpendicular to the stretching direction (non-shrinking direction) during stretching, and the heat shrinkage rate in the non-shrinking direction also increases, which is undesirable. Therefore, it is important to suppress the necking force. High-temperature stretching is known as a measure to suppress the necking force. However, if high-temperature stretching is performed to reduce the film stretching stress (suppressing the necking force), the molecular orientation in the stretching direction also decreases, the heat shrinkage rate in the main shrinkage direction decreases, and thickness unevenness worsens, which is undesirable. Furthermore, if the distance between the rolls is widened in order to slow down the deformation speed during stretching, necking occurs, which is undesirable because it results in a large difference in the properties in the width direction of the film after stretching. So far, no polyester raw material capable of overcoming the above-mentioned drawbacks has been found. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 5-33895 [Patent Document 2] Patent No. 4411556 [Patent Document 3] Patent No. 5249997 [Patent Document 4] JP 2011-79229 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention aims to provide a heat-shrinkable polyester film having a high heat shrinkage rate in the main shrinkage direction, a small change in natural shrinkage rate or shrinkage rate even when aged, a low shrinkage stress, and good thickness unevenness, and also aims to provide a raw material for obtaining the heat-shrinkable polyester film. [Means for solving the problem]

[0008] The present invention, which has solved the above problems, comprises the following: 1. An amorphous copolymer polyester raw material for films, characterized in that it satisfies the following requirements (1) to (4) and is used for film production. (1) The polyester resin has ethylene terephthalate as its main component, and contains 15 mol % or more and 30 mol % or less of neopentyl glycol when the total amount of glycol components in all polyester resin components is taken as 100 mol %. (2) The total polyester resin component contains 7 mol % or more and 15 mol % or less of diethylene glycol-derived constituent units out of a total of 100 mol % of glycol components. (3) The intrinsic viscosity of the raw material is 0.60 dl / g or more but less than 0.70 dl / g. (4) The glass transition temperature is 60°C or higher and 70°C or lower. 2. The copolymer polyester raw material for films according to 1., characterized in that when made into a film having a thickness of 30 μm, the number of defects having a size of 1 mm or more in the longitudinal or transverse direction of the film per 10 square meters is an average of 1.5 or less. 3. A copolymer polyester raw material for films according to 1 or 2, characterized in that the raw material has a melt viscosity of 180 Pa·S or less when measured at a shear rate of 6,080 / s and 250°C, and a melt viscosity of 350 Pa·S or less when measured at a shear rate of 6,080 / s and 230°C. 4. A heat-shrinkable polyester film containing the amorphous copolymer polyester raw material described in any one of 1 to 3 above and satisfying the following requirements (1) to (5): (1) The intrinsic viscosity of the film is 0.57 dl / g or more and 0.67 dl / g or less. (2) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is 55% or more and 85% or less in the main shrinkage direction of the film. (3) When the film is immersed in 80°C hot water for 10 seconds, the hot water heat shrinkage rate is between -10% and 1% in the direction perpendicular to the main shrinkage direction of the film. (4) The maximum shrinkage stress in the main shrinkage direction of the film measured under hot air at 90°C is 2 MPa or more and 7 MPa or less. (5) When a heat-shrinkable polyester film is aged for 672 hours in an atmosphere at a temperature of 30°C and a relative humidity of 65%, and then immersed in 70°C hot water for 10 seconds, the difference in hot water shrinkage rate in the main shrinkage direction of the film compared to before aging is 0% or more and 5% or less. 5. The heat-shrinkable polyester film according to 4., characterized in that the average thickness unevenness measured over a 1 m length in both the longitudinal and transverse directions of the film is 10% or less. 6. A heat-shrinkable label using the heat-shrinkable polyester film according to any one of 4. to 5. 7. A package formed by covering at least a part of the outer periphery of an object to be packaged with the heat-shrinkable label described in 6. above and then heat-shrinking it. Effect of the Invention

[0009] The heat-shrinkable polyester film of the present invention not only has a high shrinkage rate, but also shows a small decrease in shrinkage rate when measured at 70° C. after aging. Therefore, it is possible to continuously and industrially stably shrink the film under the same shrinkage conditions, regardless of whether the film is before or after aging.

[0010] The raw material of the present invention has a low intrinsic viscosity even at a resin temperature of 230°C, and therefore the melt viscosity is also low. Therefore, it can be extruded at a lower temperature than ordinary polyester raw materials. Therefore, even though it contains a large amount of diethylene glycol, with 7 mol% to 15 mol% of diethylene glycol-derived constituent units in a total amount of 100 mol%, when made into a film of a thickness of 30 μm, it is possible to reduce the number of defects of 1 mm or more in the longitudinal or transverse direction of the film to an average of 1.5 or less per 10 square meters of film.

[0011] The heat-shrinkable polyester film of the present invention not only has a high shrinkage rate, but also has low shrinkage stress and good thickness uniformity, making it suitable for thin-walled containers and allowing the provision of a heat-shrinkable film capable of packaging larger objects than ever before.

[0012] Furthermore, the heat-shrinkable polyester film of the present invention includes not only a single-layer heat-shrinkable polyester film, but also a laminated heat-shrinkable film having the heat-shrinkable polyester film layer of the present invention and laminated with a different resin layer.

[0013] Furthermore, packages wrapped with labels obtained from the heat-shrinkable polyester film of the present invention have beautiful appearances. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The heat-shrinkable polyester film of the present invention will be described in detail below. The manufacturing method of the heat-shrinkable polyester film will be described in detail later, but the heat-shrinkable film is usually obtained by conveying and stretching the film using a roll or the like. In this case, the conveying direction of the film is called the longitudinal direction, and the direction perpendicular to the longitudinal direction is called the film width direction. Therefore, the width direction of the heat-shrinkable polyester film shown below is the direction perpendicular to the roll unwinding direction, and the film longitudinal direction is the direction parallel to the roll unwinding direction.

[0015] One of the methods to obtain a film with higher shrinkage is to increase the amount of monomer components (hereinafter, simply referred to as amorphous components) that constitute units that can become amorphous components in the film. In films obtained by conventional transverse uniaxial stretching methods, it was recognized that increasing the amount of amorphous components increased the shrinkage rate accordingly. However, it was found that while simply increasing the amount of amorphous components can achieve high shrinkage, aging can cause problems such as an increase in the natural shrinkage rate and a decrease in the shrinkage rate measured at a low temperature of about 70°C. It was also found that increasing the amount of amorphous components leads to poor thickness unevenness and impairs the appearance of the film product roll. Therefore, the present inventors focused on diethylene glycol (hereinafter, also simply referred to as "DEG").

[0016] Diethylene glycol has not been actively used in the past because an increase in the amount of diethylene glycol leads to poor heat resistance and increases the discharge of foreign matter during melt extrusion. However, the present inventors have found that using diethylene glycol as a constituent unit of polyester resin reduces the stretching stress during film stretching, and furthermore, can suppress the decrease in shrinkage measured at a low temperature of about 70°C after aging.

[0017] The amorphous copolyester used for producing the heat-shrinkable polyester film of the present invention is one that contains ethylene terephthalate units as a main component. Here, "main component" means that it is 50 mol% or more of all components. The ethylene terephthalate units are preferably 50 mol% or more, more preferably 60 mol% or more, and even more preferably 70 mol% or more of the 100 mol% of the polyester constituent units.

[0018] Examples of dicarboxylic acid components other than terephthalic acid constituting the polyester of the present invention include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, and 2,6-naphthalenedicarboxylic acid, aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, and decanedicarboxylic acid, and alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid. Of the 100 mol% polyhydric alcohol components and 100 mol% polyvalent carboxylic acid components in the entire polyester resin (i.e., out of a total of 200 mol%), the terephthalic acid component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, and particularly preferably 95 mol% or more. In the present invention, it is most preferable that no dicarboxylic acid components other than terephthalic acid are contained (i.e., 100 mol% terephthalic acid).

[0019] Here, the interpretation of the above term "can be an amorphous component" will be explained in detail.

[0020] In the present invention, the term "amorphous polymer" specifically refers to a polymer that does not have an endothermic peak due to melting when measured by a DSC (differential scanning calorimeter). Amorphous polymers are not substantially crystallized, and cannot assume a crystalline state, or even if they do crystallize, the degree of crystallization is extremely low.

[0021] In the present invention, the term "crystalline polymer" refers to a polymer other than the above-mentioned "amorphous polymer", i.e., a polymer that has a melting endothermic peak in the measurement by a DSC differential scanning calorimeter. A crystalline polymer is a polymer that can be crystallized when heated, has a property capable of crystallization, or is already crystallized.

[0022] In general, a polymer in which many monomer units are bonded is an amorphous polymer when it has various conditions such as low stereoregularity, poor symmetry, large side chains, many branches, and low intermolecular cohesive force between polymers. However, depending on the state of existence, crystallization may progress sufficiently to become a crystalline polymer. For example, even if the side chain is large, if the polymer is composed of a single monomer unit, crystallization may progress sufficiently to become crystalline. Therefore, even if the monomer unit is the same, the polymer may be crystalline or amorphous, so in the present invention, the expression "unit derived from a monomer that can become an amorphous component" is used.

[0023] In the present invention, the monomer unit refers to a repeating unit constituting a polymer derived from one polyhydric alcohol molecule and one polycarboxylic acid molecule.

[0024] When a monomer unit consisting of terephthalic acid and ethylene glycol (ethylene terephthalate unit) is the main monomer unit constituting the polymer, examples of the monomer-derived unit that can become the above-mentioned amorphous component include a monomer unit consisting of isophthalic acid and ethylene glycol, a monomer unit consisting of terephthalic acid and neopentyl glycol, a monomer unit consisting of terephthalic acid and 1,4-cyclohexanedimethanol, and a monomer unit consisting of isophthalic acid and butanediol.

[0025] It is also preferable that the polyester does not contain a polyvalent carboxylic acid having a valence of three or more (for example, trimellitic acid, pyromellitic acid, and anhydrides thereof, etc.). Heat-shrinkable polyester films obtained using polyesters containing such polyvalent carboxylic acids are difficult to achieve the required high shrinkage ratio.

[0026] Examples of diol components other than the ethylene terephthalate unit constituting the polyester of the present invention include aliphatic diols such as 1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2-isopropyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 1,4-butanediol, hexanediol, neopentyl glycol, and hexanediol; alicyclic diols such as 1,4-cyclohexanedimethanol; and aromatic diols such as bisphenol A.

[0027] The amorphous copolymer polyester used for the production of the heat-shrinkable polyester film of the present invention must contain a diethylene glycol-derived constituent unit. The diethylene glycol-derived constituent unit is preferably 7 mol% or more, more preferably 8 mol% or more, even more preferably 9 mol% or more, and particularly preferably 10 mol% or more, based on 100 mol% of the polyester constituent units. The upper limit of the diethylene glycol-derived constituent unit is preferably 15 mol% or less, more preferably 14 mol% or less, and even more preferably 13 mol% or less. The diethylene glycol-derived constituent unit is a component that lowers the glass transition temperature of the polyester and increases the heat shrinkage rate of the heat-shrinkable polyester film in the low temperature range, and when the diethylene glycol-derived constituent unit is contained at 7 mol% or more, the effects of the present invention such as the reduction in the shrinkage rate measured at 70 ° C. after aging and the reduction in shrinkage stress are improved, which is preferable. On the other hand, when the diethylene glycol component is contained more than 15 mol%, the improvement effect on the reduction in the shrinkage rate measured at 70 ° C. after aging is not large, and deterioration products and defects in the film increase, which is not preferable.

[0028] In addition, the polyester has a total of 15 mol% or more, preferably 16 mol% or more, more preferably 17 mol% or more of amorphous components in 100 mol% of polyhydric alcohol components and 100 mol% of polyvalent carboxylic acid components in the entire polyester resin (i.e., in a total of 200 mol%). The upper limit of the total amorphous components is 30 mol% or less, preferably 29 mol% or less, more preferably 28 mol% or less. By setting the diethylene glycol-derived structural unit and the amount of amorphous components within the above range, a polyester with a glass transition point (Tg) adjusted to 60 to 70 ° C. can be obtained. If Tg is low, the film molecules move at room temperature and the film properties change, so 61 ° C. or more is preferable, and 62 ° C. or more is more preferable. If Tg is high, the 70 ° C. hot water shrinkage rate is low, so 69 ° C. or less is preferable, and 68 ° C. or less is more preferable.

[0029] It is preferable that the polyester does not contain a diol having 8 or more carbon atoms (e.g., octanediol, etc.) or a polyhydric alcohol having 3 or more valences (e.g., trimethylolpropane, trimethylolethane, glycerin, diglycerin, etc.). A heat-shrinkable polyester film obtained using a polyester containing these diols or polyhydric alcohols is difficult to achieve a required high shrinkage rate. It is also preferable that the polyester does not contain triethylene glycol or polyethylene glycol as much as possible. In addition, it is preferable that the polyester copolymerizes the amorphous components in 100 mol% of the polyhydric alcohol component and 100 mol% of the polycarboxylic acid component in the entire polyester resin (i.e., in a total of 200 mol%). By copolymerizing, there is no concern about raw material segregation, and it is possible to prevent changes in the film physical properties due to fluctuations in the film raw material composition. Furthermore, by copolymerizing, ester exchange proceeds, which increases the amount of amorphous components and is advantageous for increasing the shrinkage rate in the main shrinkage direction.

[0030] Various additives, such as waxes, antioxidants, antistatic agents, crystal nucleating agents, viscosity reducers, heat stabilizers, coloring pigments, coloring inhibitors, and ultraviolet absorbers, may be added to the resin forming the heat-shrinkable polyester film of the present invention, as necessary.

[0031] In the resin forming the heat-shrinkable polyester film of the present invention, it is preferable to add fine particles as a lubricant to improve the workability (slipperiness) of the film. Any fine particles can be selected, but for example, inorganic fine particles can be silica, alumina, titanium dioxide, calcium carbonate, kaolin, barium sulfate, etc., and organic fine particles can be acrylic resin particles, melamine resin particles, silicone resin particles, crosslinked polystyrene particles, etc. The average particle size of the fine particles can be appropriately selected as needed within the range of 0.05 to 3.0 μm (measured with a Coulter counter). For example, if the content of silica is 50 ppm or more and 3000 ppm or less, the average particle size of the fine particles can be adjusted to the above range. The content of silica is preferably 200 ppm or more, more preferably 300 ppm or more. If the content of silica is too high, transparency is impaired, so for films that require transparency, the content is preferably 2000 ppm or less, and more preferably 1500 ppm or less.

[0032] The method of blending the above particles into the resin forming the heat-shrinkable polyester film can be, for example, addition at any stage of the production of the polyester resin, but it is preferable to add the particles as a slurry dispersed in ethylene glycol or the like at the stage of esterification or after the completion of the transesterification reaction and before the start of the polycondensation reaction, and proceed with the polycondensation reaction. It is also preferable to blend a slurry of the particles dispersed in ethylene glycol or water or the like with the polyester resin raw material using a vented kneading extruder, or to blend the dried particles with the polyester resin raw material using a kneading extruder.

[0033] The heat-shrinkable polyester film of the present invention may be subjected to corona treatment, coating treatment, flame treatment, etc. in order to improve the adhesiveness of the film surface.

[0034] Next, the characteristics of the amorphous copolymer polyester raw material and the heat-shrinkable polyester film of the present invention will be described.

[0035] The intrinsic viscosity of the amorphous copolymerized polyester raw material of the present invention is preferably 0.6 dl / g or more and less than 0.7 dl / g. By combining the intrinsic viscosity in this range with the melt extrusion conditions described below, it is possible to adjust the intrinsic viscosity of the heat-shrinkable polyester film to 0.57 dl / g or more and 0.67 dl / g or less. If the intrinsic viscosity of the heat-shrinkable polyester film is less than 0.57 dl / g, it becomes difficult to stretch the film during the production process, and the phenomenon of breakage occurs, which is undesirable because it reduces productivity. The intrinsic viscosity of the heat-shrinkable polyester film is preferably 0.59 dl / g or more, and more preferably 0.61 dl / g or more. Although there is no problem if the intrinsic viscosity of the heat-shrinkable polyester film is higher than 0.67 dl / g, the upper limit of the intrinsic viscosity of the raw material is 0.7 dl / g, so the upper limit of the intrinsic viscosity of the film is set to 0.67 dl / g. By setting the upper limits of the intrinsic viscosity of the amorphous copolymer polyester raw material and the intrinsic viscosity of the heat-shrinkable polyester film within these ranges, as described above, it is possible to reduce the stretching stress in the longitudinal direction and suppress the necking force in the direction perpendicular to the stretching direction, particularly when producing a heat-shrinkable film whose main shrinkage direction is the longitudinal direction by roll-to-roll stretching, and it is possible to produce a film with low shrinkage stress in the longitudinal direction and good thickness unevenness.

[0036] The melt viscosity of the amorphous copolymer polyester raw material of the present invention is preferably 180 Pa·S or less when measured at a shear rate of 6080 / S and 250°C. Also, the melt viscosity is preferably 350 Pa·S or less when measured at a shear rate of 6080 / S and 230°C. If the melt viscosity is high, extrusion becomes difficult unless the resin temperature is increased, but in the case of raw materials containing a large amount of diethylene glycol as in the present invention, if the resin temperature is high, it is not preferable because a large amount of foreign matter will be produced in the film or sheet after extrusion. Therefore, the resin temperature is preferably 240°C or less, and more preferably 230°C or less. The lower limit of the resin temperature is the melting point temperature of the raw material, but the melting point of the raw material of the present invention is not clear and the material is melted at 210°C, so the lower limit is 210°C. Furthermore, if the melt viscosity is higher than 180 Pa·S when measured at 250°C, or higher than 350 Pa·S when measured at 230°C, the load on the machine that melts and extrudes the raw material increases, which is undesirable as it requires larger equipment. The melt viscosity is preferably 330 Pa·S or less when measured at 230°C, and more preferably 310 Pa·S or less. If the melt viscosity is too low, the shear stress at the discharge part of the molten resin decreases, which is undesirable as it causes uneven thickness. The melt viscosity when measured at 250°C is preferably 100 Pa·S or more, and more preferably 110 Pa·S or more.

[0037] The heat-shrinkable polyester film of the present invention is immersed in 90°C hot water for 10 seconds under no load, and then immediately immersed in 25°C±0.5°C water for 10 seconds. The heat shrinkage rate in the width direction (main shrinkage direction) of the film (i.e., hot water heat shrinkage rate at 90°C) is calculated from the lengths before and after shrinkage using the following formula 1, and is 55% or more and 85% or less. Heat shrinkage rate = {(length before shrinkage - length after shrinkage) / length before shrinkage} x 100 (%) (Formula 1)

[0038] If the hot water heat shrinkage rate in the main shrinkage direction at 98°C is less than 55%, it will not meet the requirements for a high-shrinkage film that covers the entire container (so-called full label), and since the amount of shrinkage is small, when used as a label, the label will be distorted, insufficient in shrinkage, wrinkled, loose, etc. after heat shrinkage. The hot water heat shrinkage rate at 90°C is preferably 58% or more, and more preferably 61% or more. Note that there is little requirement for a film with a hot water heat shrinkage rate in the main shrinkage direction at 90°C of more than 85%, so the upper limit of the hot water heat shrinkage rate is set to 85%.

[0039] In addition, the heat-shrinkable polyester film of the present invention has a hot water heat shrinkage rate at 80°C in the direction perpendicular to the main shrinkage direction of the film (longitudinal direction) measured in the same manner as above of -10% or more and 1% or less. If the hot water heat shrinkage rate in the direction perpendicular to the main shrinkage direction at 80°C is less than -10%, the amount of elongation of the film due to heating is too large, and it is not preferable to be unable to obtain a good shrink appearance when used as a label for a container. Conversely, if the hot water heat shrinkage rate in the direction perpendicular to the main shrinkage direction at 80°C exceeds 1%, the heat-shrinkable label will have wrinkles and distortions like rice grains, which is not preferable. The upper limit of the hot water heat shrinkage rate in the direction perpendicular to the main shrinkage direction at 80°C is preferably 0% or less.

[0040] The heat-shrinkable polyester film of the present invention has a maximum shrinkage stress of 2 MPa or more and 7 MPa or less in the main shrinkage direction of the film, measured under hot air at 90° C. The shrinkage stress is measured by the method described in the examples.

[0041] If the maximum shrinkage stress at 90°C in the main shrinkage of the film exceeds 7 MPa, this is not a problem for containers such as PET bottles, but is undesirable for thin-walled containers, as they may be crushed due to the shrinkage stress during shrinkage. The maximum shrinkage stress at 90°C is more preferably 6 MPa or less, and even more preferably 5 MPa or less. Furthermore, if the maximum shrinkage stress in the main shrinkage direction of the film at 90°C is less than 2 MPa, it is undesirable because the label may become loose and not adhere to the container when used as a label for the container. The maximum shrinkage stress at 90°C is more preferably 2.5 MPa or more, and even more preferably 3 MPa or more.

[0042] The heat shrinkable film obtained using the amorphous copolymerized polyester raw material of the present invention has, when formed into a film having a thickness of 30 μm, 1.5 or less defects having a size of 1 mm or more in the longitudinal or transverse direction of the film per 10 square meters. If the number of defects is more than 1.5, the ink will not be removed at the defective (foreign) parts during printing, which is undesirable as it will impair the appearance of the printed label. The size of the defects in the longitudinal or transverse direction of the film per 10 square meters is preferably 1 or less, more preferably 0.5 or less.

[0043] The heat-shrinkable polyester film of the present invention is preferably such that the difference in hot water shrinkage rate in the main shrinkage direction when the film is immersed in hot water at 70°C for 10 seconds after aging at a temperature of 30°C and a humidity of 65% is 0% or more and 5% or less compared to before aging (the following formula 2). If the difference in hot water shrinkage rate at 70°C before and after aging is large, the temperature conditions in the process of shrinking the film to make a label before and after aging will be different, which is not preferable. In particular, when films before and after aging are mixed due to inventory, if they are heat-shrunk industrially continuously, the appearance of the shrinkage finish will be different, which is not preferable. The difference in hot water shrinkage rate when the film is immersed in hot water at 70°C for 10 seconds after aging is preferably 4% or less compared to before aging, and more preferably 3% or less. Moreover, it is most preferable that the hot water shrinkage rate does not change before and after aging, so the lower limit is set to 0%. Difference in thermal shrinkage rate = (Hot water shrinkage rate before aging - Hot water shrinkage rate after aging) (%) (Equation 2)

[0044] The heat-shrinkable polyester film of the present invention preferably has a thickness unevenness of 10% or less, as shown by formula 3, when measured over a length of 1 m in the longitudinal and transverse directions of the film product. If the thickness unevenness is more than 10%, it is not preferable because misregistration due to wrinkles or meandering occurs when printing or processing the product roll. The thickness unevenness is preferably 8% or less, and more preferably 6% or less. Thickness unevenness = (maximum thickness - minimum thickness) ÷ average thickness × 100 (%) (Formula 3)

[0045] The heat-shrinkable polyester film of the present invention is not particularly limited, but preferably has a thickness of 5 μm to 50 μm, and more preferably has a lower limit of 6 μm.

[0046] The heat-shrinkable polyester film of the present invention can be obtained by melt-extruding the above-mentioned polyester raw material with an extruder to form an unstretched film, and then stretching the unstretched film in the width direction. The polyester can be obtained by polycondensing the above-mentioned suitable dicarboxylic acid component and diol component by a known method. In addition, chip-shaped polyester is usually used as the raw material for the film.

[0047] When melt extruding the raw resin, it is preferable to dry the polyester raw material using a dryer such as a hopper dryer or a paddle dryer, or a vacuum dryer. After drying the polyester raw material in this way, it is melted at a temperature of 230 to 270°C and extruded into a film using an extruder. For extrusion, any existing method such as a T-die method or a tubular method can be used.

[0048] The extruded sheet-like molten resin can then be quenched to obtain an unstretched film. As a method for quenching the molten resin, a method in which the molten resin is cast from a die onto a rotating drum and rapidly cooled and solidified to obtain a substantially unoriented resin sheet can be suitably adopted.

[0049] The obtained unstretched resin sheet is stretched longitudinally or transversely to have an arbitrary main shrinkage direction.

[0050] (Longitudinal stretching and relaxation after longitudinal stretching) When the film is produced by longitudinal stretching, the following methods (1) and (2) are preferably adopted, since the properties of the copolymer polyester of the present invention can be more suitably exhibited. (1) Control of longitudinal stretching conditions Transverse stretching is performed by the speed difference between rolls. It is preferable to preheat the film to a temperature of Tg or higher and Tg+20°C or lower on a heated roll, use an infrared heater to make the film temperature +5 to 20°C higher than on the roll, and stretch 3.5 to 6 times using the speed difference. If the film temperature on the roll is lower than Tg, the stretching stress increases during stretching, which is not preferable, and breakage occurs. If the temperature is higher than Tg++20°C, the film sticks to the roll, which is not preferable, and thickness unevenness becomes worse. It is also preferable to increase the film stretching temperature within the above range using an infrared heater or the like. This is because the stretching interval between rolls is short in longitudinal stretching, and the deformation speed during stretching is fast. On the other hand, in order to improve the thickness, it is preferable to increase the value of the stress ratio (tensile stress at final stretching ÷ upper yield point stress) in the stress-strain curve, so a high stretching temperature is preferable because the upper yield point stress decreases and can be controlled within an appropriate range.

[0051] (2) Relaxation in the longitudinal direction after longitudinal stretching It is desirable to heat treat the film after longitudinal stretching to relax it in the machine direction (0% means no relaxation). Relaxation slightly reduces the shrinkage rate in the machine direction, but relaxes the molecular orientation in the machine direction, making it possible to reduce the shrinkage stress. Furthermore, heat treatment at a temperature higher than the stretching temperature relaxes the molecular orientation and makes it possible to reduce the shrinkage stress. Heat treatment methods include using a heated furnace or heating the film by increasing the roll temperature after MD stretching.

[0052] (Transverse stretching and relaxation after transverse stretching) When the film is produced by transverse stretching, the following methods (3) and (4) are preferably employed, since the properties of the copolymer polyester of the present invention can be more suitably exhibited. (3) Control of transverse stretching conditions In the transverse stretching, the film is preheated to a temperature of Tg+10°C or more and Tg+25°C or less while being held by clips at both ends in the width direction in a tenter. After that, it is preferable to stretch the film 3.5 to 6 times in the width direction while cooling so that the temperature is Tg or more and Tg+9°C or less. By stretching the film in the width direction while cooling, the stress ratio (tensile stress at the final stretching ÷ upper yield point stress) in the stress-strain curve becomes higher, and thickness unevenness in the width direction can be reduced. After the transverse stretching, it is preferable to heat-treat the film at the stretching temperature +1°C to +10°C. If the heat treatment temperature is lower than the stretching temperature, the relaxation of molecular orientation is insufficient, and the shrinkage stress cannot be reduced, which is not preferable. Also, if the heat treatment temperature is higher than the stretching temperature +10°C, the shrinkage rate in the width direction decreases, which is not preferable.

[0053] (4) Relaxation in the width direction after transverse stretching In the heat treatment step, it is preferable to relax the film by 0% to 5% in the width direction while holding both ends in the width direction with clips in the tenter (0% means no relaxation). By relaxing the film, the shrinkage rate in the width direction decreases slightly, but the molecular orientation in the width direction is relaxed, making it possible to reduce the shrinkage stress. In the final heat treatment step, the film is heat treated at a temperature higher than the stretching temperature, which relaxes the molecular orientation and makes it possible to reduce the shrinkage stress.

[0054] The packaging body of the present invention is formed by covering at least a part of the outer periphery of the packaging object with a label having a perforation or a notch obtained from the heat-shrinkable polyester film of the present invention and heat-shrinking it. Examples of the packaging object include PET bottles for beverages, various bottles, cans, plastic containers for sweets and lunch boxes, and paper boxes. In addition, when the label obtained from the heat-shrinkable polyester film is heat-shrunk to cover the packaging object, the label is usually heat-shrunk by about 5 to 70% to be adhered to the packaging body. In addition, the label to be covered on the packaging object may or may not be printed.

[0055] The method for producing a label from the heat-shrinkable polyester film of the present invention is to apply an organic solvent to one side of a rectangular film, slightly inward from the edge, and then immediately roll the film, overlap and glue the edges together to form a label, or to apply an organic solvent to one side of a rolled film, slightly inward from the edge, and then immediately roll the film, overlap and glue the edges together to form a tube, which is then cut into a label. As the organic solvent for adhesion, cyclic ethers such as 1,3-dioxolane or tetrahydrofuran are preferred. Other examples include aromatic hydrocarbons such as benzene, toluene, xylene, and trimethylbenzene, halogenated hydrocarbons such as methylene chloride and chloroform, and phenols such as phenol, or mixtures thereof. EXAMPLES

[0056] Next, the present invention will be specifically described using examples and comparative examples, but the present invention is not limited to the embodiments of these examples and can be appropriately modified within the scope of the present invention. The film evaluation method is shown below.

[0057] [Heat shrinkage rate (hot water heat shrinkage rate)] The film was cut into a 10 cm x 10 cm square and immersed in warm water of a specified temperature ± 0.5°C for 10 seconds without load to allow it to shrink thermally. It was then immersed in water at 25°C ± 0.5°C for 10 seconds and pulled out of the water, after which the longitudinal and transverse dimensions of the film were measured and the thermal shrinkage percentage was calculated according to the following formula (1). Heat shrinkage rate = {(length before shrinkage - length after shrinkage) / length before shrinkage} x 100 (%) Formula (1)

[0058] [Difference in thermal shrinkage rate before and after aging] The hot water shrinkage at 70°C was calculated using the same method as in formula (1) above. After that, the unmeasured film was aged for 672 hours in an environmental test room at a temperature of 30°C and a humidity of 65%, and then the film was similarly measured in hot water at 70°C. The difference in the thermal shrinkage was calculated according to the following formula (2). Difference in thermal shrinkage rate = (Hot water shrinkage rate before aging - Hot water shrinkage rate after aging) (%) (Equation 2)

[0059] [Shrinkage stress] A strip-shaped film sample having a length of 200 mm in the main shrinkage direction (width direction) and a width of 20 mm was cut out from the heat-shrinkable film, and the shrinkage stress was measured using a Tesilon universal testing machine PTM-250 (registered trademark of Orientec Co., Ltd.) with a heating furnace manufactured by Toyo Baldwin Co., Ltd. (currently Orientec Co., Ltd.). The heating furnace of the strength and elongation measuring machine was heated to 90°C in advance, and the distance between the chucks for holding the film sample was 100 mm. When attaching the sample to the chuck of the strength and elongation measuring machine, the air blowing of the heating furnace was stopped once, the door of the heating furnace was opened, and 25 mm each of both ends of the sample with a length of 150 mm was clamped between the chucks, the distance between the chucks was set to 100 mm, and the sample was fixed without loosening so that the distance between the chucks and the length direction of the sample coincided and the sample was horizontal. After attaching the sample to the chuck, the door of the heating furnace was quickly closed, and the air blowing was resumed. The point at which the door of the heating furnace was closed and air flow was resumed was regarded as the starting point for measuring the shrinkage stress, and the maximum value after measuring for 30 seconds was calculated as the shrinkage stress (MPa).

[0060] [Thickness Unevenness] The film was sampled in a strip of 1 m in the direction to be measured and 40 mm in the width direction, and the thickness was continuously measured along the longitudinal direction of the film sample at a speed of 5 (m / min) using a continuous contact type thickness meter manufactured by Micron Measurement Instruments Co., Ltd. The thickness unevenness of the film was calculated using the following formula 3. Thickness unevenness = (maximum thickness - minimum thickness) ÷ average thickness × 100 (%) (Formula 3)

[0061] [Limiting viscosity] 0.2 g of polyester was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)), and the viscosity was measured using an Ostwald viscometer at 30° C. The unit is dl / g.

[0062] [Melt Viscosity] Using a Capillograph 1D PMD-C (Toyo Seiki Seisakusho Co., Ltd.), the resin was heated to the specified temperature (250°C, 230°C) and measurements were carried out in accordance with JIS K7199 at a shear rate of 6080 / s.

[0063] [How to count the number of defects] The film was sampled to a size of 50 cm in the width direction and 50 cm in the length direction. The cut film was placed on a tabletop film orientation viewer (manufactured by Unitika) and polarized light was applied. The number of defects of 1 mm or more was then counted using a 10x magnifying glass. The number of defects on a total of 120 pieces of film (30 square meters) was counted in the same manner. The average number of defects per 10 square meters of film was then calculated using the following formula 4. Average number of defects = total number of defects / 3 (defects / 10 square meters) (Equation 4)

[0064] [Amorphous unit content] The heat-shrinkable film was scraped off with a razor blade to perform sampling. Approximately 5 mg of the sampled film was dissolved in 0.7 ml of a mixed solution of deuterated chloroform and trifluoroacetic acid (volume ratio 9 / 1), and the amount of amorphous units (neopentyl glycol units and cyclohexanedimethanol units in the following example) was calculated using 1H-NMR (variant, UNITY50), and the molar percentage (the sum of the proportion of polyol-type amorphous units when the polyol units are 100 mol % and the proportion of polycarboxylic acid-type amorphous units when the polycarboxylic acid units are 100 mol %) was determined. The product of the amount of polymer in the film (mass %) and the above mol % was taken as the content of amorphous units (mass mol %).

[0065] [Tg (glass transition temperature)] Using a differential scanning calorimeter (model: DSC220) manufactured by Seiko Denshi Kogyo Co., Ltd., 5 mg of unstretched film was heated from -40°C to 120°C at a heating rate of 10°C / min, and the endothermic curve obtained was used to determine the glass transition temperature (Tg). The temperature at the intersection of the extension of the baseline below the glass transition temperature and the tangent showing the maximum slope at the transition section was taken as the glass transition temperature (Tg).

[0066] [Shrinkage finish] A three-color print was applied to the heat-shrinkable film in advance using green, gold, and white inks from Toyo Ink Mfg. Co., Ltd. Then, both ends of the printed film were glued with dioxolane to prepare a cylindrical label (a label with the main shrinkage direction of the heat-shrinkable film as the circumferential direction), which was then cut. The diameter of the label in the shrinkage direction was 70 mm. Then, using a steam tunnel (model: SH-1500-L) manufactured by Fuji Astec Inc., the label was attached to a 500 ml PET bottle (body diameter 62 mm, minimum diameter of neck 25 mm) by heat shrinking it at a zone temperature of 90°C for 5 seconds. When attaching the label, the neck was adjusted so that the 30 mm diameter part was at one end of the label. The finish after shrinkage was evaluated visually, with the following criteria:

[0067] Label shrinkage distortion To evaluate the finish after shrinkage, the distortion of the top of the attached label in the 360-degree direction was measured using a gauge to determine the maximum distortion value. Evaluation was made according to the following criteria. ○: Maximum distortion less than 1.5 mm ×: Maximum distortion 1.5mm or more

[0068] [Label shrinkage is insufficient] The above-mentioned label shrinkage state was evaluated according to the following criteria. ○: The label is shrunk without any slack between the attached label and the container. ×: There is slack between the label and the container due to insufficient shrinkage.

[0069] [Wrinkles on label] Under the same conditions as those for the shrinkage distortion of the label described above, the occurrence of wrinkles was evaluated according to the following criteria. ○: The number of wrinkles larger than 1.5 mm is 2 or less. ×: 3 or more wrinkles measuring 1.5 mm or more.

[0070] [Shrinkage finish after aging] After aging for 672 hours under conditions of 30°C and 65% humidity, the heat-shrinkable film was printed in three colors using green, gold, and white inks manufactured by Toyo Ink Mfg. Co., Ltd. Then, both ends of the printed film were glued with dioxolane to prepare a cylindrical label (a label with the main shrinkage direction of the heat-shrinkable film as the circumferential direction) and cut. The diameter of the label in the shrinkage direction was 70 mm. Then, using a steam tunnel (model: SH-1500-L) manufactured by Fuji Astec Inc., the label was attached to a 500 ml PET bottle (body diameter 62 mm, minimum diameter of neck part 25 mm) by heat shrinking it at a zone temperature of 90°C for 5 seconds. Note that when attaching, the neck part was adjusted so that the 30 mm diameter part was at one end of the label. The finish after shrinkage was evaluated visually, with the following criteria: The evaluation of shrinkage finish was the same as for "label shrinkage distortion," "insufficient label shrinkage," and "label wrinkles" described above.

[0071] <Preparation of polyester raw materials> Using dimethyl terephthalate (DMT) and each of the glycol components described below, raw materials A to H were obtained by a known method of carrying out polycondensation via ester exchange. Raw material A: Polyester consisting of 25 mol% neopentyl glycol, 12 mol% diethylene glycol, 63 mol% ethylene glycol, and terephthalic acid. Intrinsic viscosity: 0.69 dl / g. Raw material B: Polyester consisting of 30 mol% neopentyl glycol, 8 mol% diethylene glycol, 62 mol% ethylene glycol, and terephthalic acid. Intrinsic viscosity: 0.60 dl / g. Raw material C: Polyester consisting of 18 mol% neopentyl glycol, 15 mol% diethylene glycol, 67 mol% ethylene glycol, and terephthalic acid. Intrinsic viscosity: 0.65 dl / g. Raw material D: Polyester consisting of 25 mol% neopentyl glycol, 5 mol% diethylene glycol, 70 mol% ethylene glycol, and terephthalic acid. Intrinsic viscosity: 0.65 dl / g. Raw material E: Polyester consisting of 11 mol% neopentyl glycol, 12 mol% diethylene glycol, 77 mol% ethylene glycol, and terephthalic acid. Intrinsic viscosity: 0.65 dl / g. Raw material F: Polyester consisting of 18 mol% neopentyl glycol, 15 mol% diethylene glycol, 67 mol% ethylene glycol and terephthalic acid. Intrinsic viscosity: 0.85 dl / g. In addition, when producing the polyester, SiO2 (Silysia 266 manufactured by Fuji Silysia Co., Ltd.) was added as a lubricant at a ratio of 600 ppm to the polyester. In the table, EG is ethylene glycol, DEG is diethylene glycol, and NPG is neopentyl glycol. Each polyester was appropriately cut into chips.

[0072] The compositions of the polyester raw materials used in the Examples and Comparative Examples, and the resin compositions and production conditions of the films in the Examples and Comparative Examples are shown in Tables 1 and 2, respectively.

[0073] [Table 1]

[0074] [Table 2]

[0075] Example 1 Raw material A was put into the extruder. The resin was melted at 270°C, extruded from a T-die while being cooled to 230°C, and then wrapped around a rotating metal roll cooled to a surface temperature of 25°C to rapidly cool, thereby obtaining an unstretched film having a thickness of 146 μm. The take-up speed of the unstretched film at this time (the rotation speed of the metal roll) was about 20 m / min. The Tg of the unstretched film was 68°C. The unstretched film obtained was introduced into a longitudinal stretching machine, preheated with a roll having a surface temperature of Tg+7°C, and stretched 5 times with an infrared heater at a film temperature of Tg+22°C. The film after longitudinal stretching was introduced into a heating roll having a surface temperature of Tg+12°C after stretching, and relaxed in the longitudinal direction by 3% using the speed difference between the rolls. The film after relaxation was cooled with a cooling roll having a surface temperature of Tg-40°C. Thereafter, both edges were cut off and the film was wound into a roll with a width of 500 mm, thereby continuously producing a uniaxially oriented film having a thickness of 30 μm over a specified length. The properties of the film obtained were evaluated by the above-mentioned method. The evaluation results are shown in Table 3. There was little change in the physical properties before and after aging, and the results were good.

[0076] Example 2 A film having a thickness of 30 μm was produced in the same manner as in Example 1, except that raw material A was changed to raw material B. Tg was 69° C. The evaluation results are shown in Table 3. The results were as good as in Example 1.

[0077] Example 3 A film having a thickness of 30 μm was produced in the same manner as in Example 1, except that raw material A was changed to raw material C. Tg was 67° C. The evaluation results are shown in Table 3. The results were as good as in Example 1.

[0078] Example 4 Raw material A was put into the extruder. The resin was melted at 270°C, extruded from a T-die while being cooled to 230°C, and then wound around a rotating metal roll cooled to a surface temperature of 25°C to rapidly cool, thereby obtaining an unstretched film having a thickness of 146 μm. The take-up speed of the unstretched film at this time (the rotation speed of the metal roll) was about 20 m / min. The Tg of the unstretched film was 68°C. The obtained unstretched film was introduced into a tenter, preheated to a surface temperature of Tg+17°C, and then stretched 5 times in the width direction while being cooled so that the surface temperature of the film became Tg+5°C. Next, the film was heated to a surface temperature of Tg+11°C, and relaxed by 3% in the width direction. After that, the film was cooled, both edges were cut and removed, and the film was wound into a roll with a width of 1000 mm, thereby continuously producing a uniaxially stretched film having a thickness of 30 μm over a predetermined length. The properties of the obtained film were evaluated by the above-mentioned method. The evaluation results are shown in Table 3. There was little change in physical properties before and after aging, and the results were good.

[0079] Example 5 A film having a thickness of 30 μm was produced in the same manner as in Example 4, except that raw material A was changed to raw material B. Tg was 69° C. The evaluation results are shown in Table 3. The results were as good as in Example 4.

[0080] Example 6 A film having a thickness of 30 μm was produced in the same manner as in Example 1, except that raw material A was changed to raw material C. Tg was 67° C. The evaluation results are shown in Table 3. The results were as good as in Example 4.

[0081] Comparative Example 1 A 30 μm-thick film was produced in the same manner as in Example 1, except that raw material A was changed to raw material D. The evaluation results are shown in Table 3. Compared to Example 1, the shrink finish before aging was good, but the longitudinal shrinkage rate at 70° C. after aging was low (the decrease due to aging was large), and when shrink finishing was performed under the same conditions as before aging, the shrink finish was poor.

[0082] Comparative Example 2 A film having a thickness of 30 μm was produced in the same manner as in Example 1, except that raw material A was changed to raw material E. The evaluation results are shown in Table 3. Compared to Example 1, the longitudinal shrinkage rate at 90° C. was low, and the shrink finish was poor.

[0083] Comparative Example 3 Raw material A was changed to raw material F. The melting temperature and extrusion temperature of the raw material were set to 270°C. This is because the intrinsic viscosity of the raw material was high, and a low extrusion temperature would have placed a large load on the extrusion machine, making extrusion difficult. Apart from that, a film with a thickness of 30 μm was produced in the same manner as in Example 3. The evaluation results are shown in Table 3. Compared to Example 3, the shrinkage stress was high and the shrink finish was poor. There were also many defects.

[0084] [Table 3] [Industrial Applicability]

[0085] The heat-shrinkable polyester film of the present invention has a high heat shrinkage rate, but the decrease in heat shrinkage rate after aging is small, and it has few defects, so it can be suitably used for label applications. Packages such as containers obtained by using the heat-shrinkable polyester film of the present invention as a label have beautiful appearances. In addition, the amorphous copolymerized polyester raw material for film of the present invention is suitably used for producing the heat-shrinkable polyester film.

Claims

1. A heat-shrinkable polyester film containing an amorphous copolymer polyester raw material for a film satisfying the following requirements (1) to (5), and satisfying the following requirements (6) to (8). (1) The polyester resin has ethylene terephthalate as its main constituent component, and contains neopentyl glycol in an amount of 15 mol % to 30 mol % when the total amount of glycol components in all polyester resin components is taken as 100 mol %. (2) The total polyester resin component contains 7 mol % or more and 15 mol % or less of diethylene glycol-derived constituent units per 100 mol % of the total amount of glycol components. (3) The intrinsic viscosity of the raw material is 0.60 dl / g or more and less than 0.70 dl / g. (4) The terephthalic acid component is 100 mol % out of 100 mol % of the polyhydric alcohol component and 100 mol % of the polycarboxylic acid component in the entire polyester resin. (5) The glass transition temperature is 60°C or higher and 70°C or lower. (6) It does not contain trivalent or higher polyvalent carboxylic acids or their anhydrides. (7) Contains inorganic or organic fine particles. (8) The average thickness unevenness measured over a 1 m length in the longitudinal and transverse directions of the film is 10% or less.

2. 2. The heat-shrinkable polyester film according to claim 1, characterized in that the number of defects measuring 1 mm or more in the longitudinal or transverse direction of the film per 10 square meters of the film in a thickness of 30 μm is an average of 1.5 or less.

3. 2. The heat-shrinkable polyester film according to claim 1, characterized in that the raw material has a melt viscosity of 180 Pa·S or less when measured at a shear rate of 6,080 / S and 250°C, and a melt viscosity of 350 Pa·S or less when measured at a shear rate of 6,080 / S and 230°C.

4. The heat-shrinkable polyester film according to claim 1, further satisfying any one of the following requirements (9) to (13): (9) The intrinsic viscosity of the film is 0.57 dl / g or more and 0.67 dl / g or less. (10) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is 55% or more and 85% or less in the main shrinkage direction of the film. (11) When the film is immersed in 80°C hot water for 10 seconds, the hot water heat shrinkage rate is -10% or more and 1% or less in the direction perpendicular to the main shrinkage direction of the film. (12) The maximum shrinkage stress in the main shrinkage direction of the film measured under hot air at 90°C is 2 MPa or more and 7 MPa or less. (13) A heat-shrinkable polyester film is aged for 672 hours in an atmosphere having a temperature of 30° C. and a relative humidity of 65%, and then immersed in hot water at 70° C. for 10 seconds. The hot water heat shrinkage rate in the main shrinkage direction of the film is 0% or more and 5% or less compared to the shrinkage rate before aging.

5. A heat-shrinkable label using the heat-shrinkable polyester film according to any one of claims 1 to 4.

6. A package formed by covering at least a part of the outer periphery of an object to be packaged with the heat-shrinkable label according to claim 5 and then heat-shrinking the label.

Citation Information

Patent Citations

  • Method of oxidizing titaniumm containing ore

    JP1977049997A

  • Shrink polyester film of improved surface property

    JP1992164930A

  • Cap

    JP1993033895A

  • Shrinkable polyester film

    JP1995053737A

  • Heat-shrinkable polyester film

    JP2011079229A